Evaluación de las variables que afectan el fracturamiento hidráulico en la zona norte del Campo Castilla mediante un análisis pozo a pozo, para la selección de futuros candidatos (2019)
The project focuses on evaluating the variables that affect hydraulic fracturing, in the Northern Zone of the Castilla Field. Through a broad comparison, reservoir variables and stimulation variables are evaluated, identifying which ones affect fracture performance. Finally, the characteristics that will make hydraulic fracturing a successful stimulation, selecting future candidates, are determined.